STRATEGI PEMASARAN PERSONALIZED RECOMMENDATION DALAM MENINGKATKAN RETENSI PELANGGAN - Yeni Yeni; Damaris Y. Koli; Rudy Irwansyah; Alya Elita Sjioen; Eva Desembrianita (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to determine the effectiveness of personalized recommendation marketing strategies in increasing customer retention. This research approach collects data through literature studies, which involve reading literature from various sources including books, articles, journals, and reports using qualitative and deductive approaches. The findings in this study are that personalized recommendation marketing strategies have proven effective in increasing customer retention. By using email marketing, website personalization, mobile applications, e-commerce and marketplaces, and social media Ads, companies can build closer relationships with customers, increase loyalty, and extend the customer life cycle in the business ecosystem.